Judges Existencing In The Judicial Process Of Narcotics Criminal Actors - Diyono Diyono; Amin Purnawan (Law Development Journal, 2020)
Aim in this study, namely to study and analyze the existence of judges in the trial of narcotics offenders? In this study the authors used a sociological juridical method with a descriptive analytical research specification. The data used for this research are primary and secondary data. Based on the results of the research with the conclusion that the existence of judges in the implementation of the narcotics crime court based on the analysis in case Number 70 / Pid.Sus / 2018 / PN Mgg, it is not wrong to be categorized as someone who thinks scientifically. As seen in the decision making, where the judge does not solely work to make and determine decisions by observing and completely applying abstract legal rules, but judges always see the problems faced in a broader context. Judging from the judge's consideration in seeing the case of the defendant Carolina Umarela by looking at things that were burdensome.